Evaluation of the Analgesic Activity of Earthworm Gel (Lumbricus rubellus) in Male Mice with Formalin-Induced Pain Model - Yovita Mercya; Ayu Amisa Fajrianti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Inflammatory pain is one of the body’s defense mechanisms, characterized by redness, swelling, and pain due to the release of inflammatory mediators. Nonsteroidal anti-inflammatory drugs (NSAIDs), such as diclofenac sodium, are commonly used topically to relieve pain but may cause local side effects with long-term use. Therefore, a safer, natural-based alternative is needed. Earthworms (Lumbricus rubellus) are known to contain polyphenols and lumbrokinase, which have anti-inflammatory and analgesic properties. This study aimed to evaluate the effectiveness of earthworm gel as a topical analgesic in male mice (Mus musculus) induced with formalin. A total of 24 mice were divided into four groups: untreated, gel base, diclofenac sodium gel, and 5% earthworm gel. Pain response was assessed by measuring the duration of licking behavior at two key phases: acute pain (0–5 minutes) and late inflammatory pain (25–30 minutes). Statistical analysis using the Kruskal-Wallis and Mann–Whitney U tests showed that earthworm gel significantly reduced licking duration in the inflammatory phase, with effectiveness comparable to diclofenac sodium gel. These findings support the potential of earthworm gel as a safe and effective natural alternative for managing inflammatory pain topically.